2021
DOI: 10.1021/acs.chemmater.1c03712
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controllable Synthesis of Ultrathin Molybdenum Nitride Crystals Via Atomic Substitution of MoS2

Abstract: MXenes are emerging members in the two-dimensional (2D) material family and are highlighted by their high electrical conductivity. Among different MXenes, molybdenum-based MXenes, especially molybdenum nitrides (MoN x ), are rarely accessible through the common synthetic approach of selective etching due to the absence of stable MAX phase precursors. In this work, we apply the atomic substitution approach to synthesize two phases of ultrathin nonlayered molybdenum nitrides (i.e., Mo5N6 and δ-MoN) from 1.6 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…[ 2 ] Unlike layered 2D materials (L2DMs), where each crystalline layer is held together by weak van der Waals interactions, NL2DMs are formed by strong covalent bonds in all three dimensions. [ 3 ] Owing to the multibody interactions, NL2DMs have demonstrated amazing physical properties in electronic transport, [ 4 ] thermal conductance, [ 5 ] heat capacity [ 6 ] as well as quasi‐particle dynamics, [ 7 ] showing great performance in electronics, [ 8 ] optoelectronics, [ 9 ] and energy storage. [ 10 ] Moreover, besides the clear benefit of a large exposed surface, the introduction of 2D morphology to nonlayered materials could also bring large structural distortion and low‐coordinated surface atoms with abundant dangling bonds, which are particularly favored in various catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Unlike layered 2D materials (L2DMs), where each crystalline layer is held together by weak van der Waals interactions, NL2DMs are formed by strong covalent bonds in all three dimensions. [ 3 ] Owing to the multibody interactions, NL2DMs have demonstrated amazing physical properties in electronic transport, [ 4 ] thermal conductance, [ 5 ] heat capacity [ 6 ] as well as quasi‐particle dynamics, [ 7 ] showing great performance in electronics, [ 8 ] optoelectronics, [ 9 ] and energy storage. [ 10 ] Moreover, besides the clear benefit of a large exposed surface, the introduction of 2D morphology to nonlayered materials could also bring large structural distortion and low‐coordinated surface atoms with abundant dangling bonds, which are particularly favored in various catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the high conductivity of MoN which can be utilized as desired electrode materials for semiconducting MoS 2 FETs, , we further apply a mask-assisted conversion method to fabricate the atomically bonded MoS 2 –MoN lateral heterostructures with a designed pattern for the study of electrical properties. As shown in Figure a, a 30-nm thick Al 2 O 3 film as a mask is deposited on the patterned region of a three-layered exfoliated MoS 2 flake via e-beam evaporation. , The sample is then heated up to 720 °C under the ammonia atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we realized ultrathin transition metal nitrides (TMNs) such as MoN x , WN x , and TiN x via atomic substitution of sulfur atoms in layered transition metal dichalcogenides (TMDs) such as MoS 2 , WS 2 , and TiS 2 , with nitrogen atoms. , The obtained ultrathin TMNs inherited the morphology of the TMDs and were characterized as highly crystalline without stratiform structures. This atomic substitution method provides a viable approach to integrate TMDs and TMNs together through an in situ chemical conversion process on a solid-state substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al investigated the electrical properties of two MoN x MXene phases, namely Mo 5 N 6 and δ-MoN. 68 The study reported that the formation of ohmic contact between nitride MXenes and Cr/Au electrodes is beneficial for developing electronic devices. Mo 5 N 6 and δ-MoN achieved high electrical conductivities of 229.6 and 3126 S cm −1 , respectively, with a minor loss in conductivity after four weeks under normal room conditions.…”
Section: Applicationsmentioning
confidence: 99%